Revisiting the child health-wealth nexus - Fakir, Adnan M. S. (© 2016 The Author(s)., 2016)
This article was published in Health Economics Review [©2016 The Author(s).] and the definite version is available at: https://healtheconomicsreview.springeropen.com/articles/10.1186/s13561-016-0120-8 The article website is at: https://healtheconomicsreview.springeropen.com